The Effect of Packaging Design, Product Quality, and Brand Image on Buying Interest in Wila Products in Surabaya City - Amaliyah, Febby Dzurrotul; Kusuma, Yanda Bara (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the influence of packaging design, product quality, and brand image on consumer purchasing interest in Wila, a healthy snack made from pumpkin. With the increasing trend of healthy lifestyles, consumers are now more selective in choosing products, including in the snack category. Wila is present as a local healthy snack solution that prioritizes nutritional value and sustainability. This study uses a quantitative approach by distributing questionnaires to 100 respondents who have known or tried Wila products. The sampling technique used was purposive sampling, and the analysis method used was multiple linear regression through SPSS. The results of the study indicate that packaging design, product quality, and brand image partially and simultaneously have a significant effect on consumer purchasing interest.